# Which is the easy method to solve the polynomial equation of degree 4 i.e., bi-quadratic? Please explain it... Very urgent....!

2
by ankitkumar0102

2015-04-05T16:45:39+05:30
Put x=1,-1,2,-2,3,-3 n in the option in which f(x)=0, choose it n make factor like if putting x =1, u get f(x)=0, the factor will be (x-1).. then divide the equ with x-1 n u ll get a cubic equ, apply same putting on it n again divide the factor you came across second time wid cubic equ, u ll get a quadratic equ n simply do its middle splitting.. Hope it helps..
thanks @ Anniieee this is very lengthy method. is their any more method by which i can solve it?
Yp.. it is lengthy..
Welcome..
2015-04-05T23:06:27+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
To solve:    f(x) = x⁴ + a x³ + b x² + c x + d = 0    --- (1)

one way is to check f(x = -1), f(x = -2), f (x = -3) or f(0), or f(x=1) or f(x=2) etc if that is zero.  Then we have a factor like (x- k), if  f (x = k) = 0.

Then we can write f(x) = (x - k) [ x³ + (a+k) x² + (b+ak+k²) x - d / k ]
Now, the cubic equation could be again checked if, you could find some factors.  Or, one could try the way a cubic equation is solved or reduced into a quadratic equation.  There are standard formulas for solving cubic equations.
====================
We could try other means of reducing the quartic equation into a cubic equation and then solve that ..

f (x) = x⁴  + a x³ + b x² + c x + d = 0    -- (1)

let z = x + a/4,  then    z⁴ = x⁴ + 4 x³ a/4 + 6 x² a²/4²  + 4 x a³/4³ + a⁴/4⁴
x⁴ + a x³ =  z⁴ - 3 x²a²/8 -- xa³/16 - a⁴/256
Substitute   x = z - a/4

f(x) = (z - a/4)⁴ + a(z - a/4)³ + b (z - a/4)² + c (z - a/4) + d = 0
=  z⁴ - z³ a + 3 z² a²/8 - z a³/16 + a⁴/256 + a z³ - 3a² z²/4 + 3 a³ z/16 - a⁴ z/64
+ b z² - ab z/2 + a²b/16 + c z - ac/4 + d = 0

F(z) = z⁴ + z² (b -3a²/8) + z (c+ a³/8 - a⁴/64 - ab/2) + (a⁴/256 +a²b/16 -ac/4 +d) = 0    -- (2)
Let  A = b - 3a²/8      B = c+a³/8 - a⁴/64 -ab/2
C = d + a⁴/256 + a²b/16 - ac/4

F(z) = z⁴ + A z² + B z + C = 0          rewrite it as,        --- (3)
=>  (z² + A)² = A z² + A² - B z - C

Then  (z² + A + y)² = (z²+A)²  + y² + 2 y (z² + A)            --- (4)
= A z² + A² - Bz - C + y² + 2 y z² + 2 A y
= z² (A + 2y) - B z + (y² + 2Ay + A² - C)      -- (5)

2 Roots of this equation are equal if the discriminant on the RHS is 0.  So RHS becomes a perfect square.  LEt us choose y such that Discriminant = 0.
Discr = B² - 4 (A+2y) (y² + 2Ay + A² - C)  = 0        --- (6)
= B² - 4 [ 2 y³ + 5A y² + 2 y (2A² - C) + A³ - AC ] = 0
= B² - 8 y³ - 20 A y² - 8 (2A²-C) y - 4(A³- AC)  = 0
=>  y³ + (A²+4A)/2 y² + (2A² -C) y + [(A³-AC) /2 - B²/8] = 0      -- (7)

Call  (A²+4A)/2  = P   ;   2A²-C = Q  ;    (A³-AC)/2 - B²/8 = R

This is a cubic equation.  Rewrite it as :

G(y) = y³ + P y² + Q y + R = 0                       -- (8)
now   substitute u = y + P/3 ,  so  y =  u - P/3
F(y) = T(u) = (u-P/3)³ + P(u- P/3)² + Q (u - P/3) + R = 0
T(u) = u³ - 3 u² P/3 + 3 u P²/9 + P u² - 2P²u/3 +P³/9 + Q u -PQ/3 + R = 0
= u³ + u (Q - P²/3) + (P³/9 - PQ/3 +R)  = 0

Call   (Q - P²/3) = - 3p       and  (P³/9 - PQ/3 + R) = - 2 q

T(u) = u³ - 3p u - 2q = 0              -- (9)
Three Solutions for this are:

From the solutions u_0, u_1, u_2, we find y = u - P/3.
For these values of y we have the equation (7) satisfied.  Hence, the discriminant of RHS of equation (5) is zero. The solution for equation (5) is:

(z²+A+y)² = (A+2y) [ z - B/(2A+4y) ]²
= [ √(A+2y) z - B / {2√(A+2y) }]²
Hence,
[z²+A+y+√(A+2y) z - B/ {2√(A+2y)} ] [z²+A+y-√(A+2y) z +B/ {2√(A+2y)}] = 0

Each factor gives two values of z.  So we get 4 solutions for z.
Then substitute x = z - a/4  to get the 4 solutions of equation (1).